Efektivitas Penerapan Relaksasi Benson Dalam Menurunkan Kecemasan Pada Pasien Pre-Operasi: Studi Kasus - Atha Rahma Talitha; Ambar Relawati (Jurnal Medika Nusantara, 2023)
The pre-operative period is strongly associated with increased anxiety levels amongst patients, resulting in emotional, cognitive, or physiological responses. Anxiety in patients that is not managed properly can cause psychological and physical changes, namely an increase in sympathetic nerve work associated with increased breathing frequency, heart rate, blood pressure, and cold sweats. The Benson relaxation method is one of the nursing interventions in the form of relaxation that focuses the mind by combining the beliefs of each individual. Benson relaxation is a subjective stress management method that can have the effect of reducing anxiety levels, mood disorders, improving sleep quality, and reducing pain. This case study aims to determine the effectiveness of the application of Benson relaxation in reducing anxiety in pre-operative patients. The methodology utilised in this paper is a case study that examined the application of Benson relaxation interventions before surgery during 2 sessions of 20-35 minutes applying the Hamilton Anxiety Rating Scale (HAM-A) instrument to assess the patient's anxiety level. The results of this case study indicate that the provision of Benson relaxation therapy to both respondents proved effective in reducing anxiety levels before surgery as evidenced by the average decrease in HAM-A scores for both respondents of 6.5 from moderate to mild anxiety.